2012
DOI: 10.1016/j.bpj.2012.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Stiffness Tomography on Living Arabidopsis thaliana Cells Reveals the Mechanical Properties of Surface and Deep Cell-Wall Layers during Growth

Abstract: Cell-wall mechanical properties play a key role in the growth and the protection of plants. However, little is known about genuine wall mechanical properties and their growth-related dynamics at subcellular resolution and in living cells. Here, we used atomic force microscopy (AFM) stiffness tomography to explore stiffness distribution in the cell wall of suspension-cultured Arabidopsis thaliana as a model of primary, growing cell wall. For the first time that we know of, this new imaging technique was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
94
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 54 publications
12
94
3
1
Order By: Relevance
“…The images of the cells recorded in quantitative-imaging mode (27, 28) allow analysis of all the force curves recorded in a single image (n ϭ 65,536). By applying a mask, thanks to the analysis software (OpenFovea [34,35]), only the force curves corresponding to the cells are extracted, leading to the elasticity maps presented in Fig. 3a, b, and c. In all the elasticity maps presented in this study, each pixel corresponds to a force curve that has been converted into an indentation curve and fitted with a Hertz model, from which a Young modulus (YM) value was extracted.…”
Section: Resultsmentioning
confidence: 99%
“…The images of the cells recorded in quantitative-imaging mode (27, 28) allow analysis of all the force curves recorded in a single image (n ϭ 65,536). By applying a mask, thanks to the analysis software (OpenFovea [34,35]), only the force curves corresponding to the cells are extracted, leading to the elasticity maps presented in Fig. 3a, b, and c. In all the elasticity maps presented in this study, each pixel corresponds to a force curve that has been converted into an indentation curve and fitted with a Hertz model, from which a Young modulus (YM) value was extracted.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, quantitative force-volume mapping (QFM) was adapted to plant cell wall measurements utilizing continuous force curve recording and therefore solving the problem of heterogeneity observation by imaging the topography with the associated E and PI mappings. Studies on Arabidopsis thaliana reported different characteristic modes of deformation and a spatial distribution of the elastic moduli across the surface (Yakubov et al, 2016), while Radotic et al (2012) showed the changes in stiffness of the cell walls at different phases of growth. In addition, new innovative AFM techniques such as mode synthesized AFM (MSAFM) (Tetard et al, 2010(Tetard et al, , 2011 and hybrid photonic force microscopy (HPFM) (Tetard et al, 2015) have been FiGURe 1 | Chemical steps for delignification process starting from a cryotomed young poplar.…”
Section: Structurementioning
confidence: 99%
“…Several groups have recently achieved mechanical measurements made at a subcellular resolution in plants (Milani et al, 2011;Peaucelle et al, 2011;Fernandes et al, 2012;Radoti c et al, 2012;RoutierKierzkowska et al, 2012) using scaled-down indentation methods (Geitmann, 2006;Hayot et al, 2012;Milani et al, 2013;Routier-Kierzkowska and Smith, 2013), wherein one quantifies the force needed to push down on a sample to a prescribed depth. These studies have revealed spatiotemporal patterns of stiffness, notably in tissues (Milani et al, 2011;Peaucelle et al, 2011;Fernandes et al, 2012;RoutierKierzkowska et al, 2012).…”
mentioning
confidence: 99%